1986
DOI: 10.1002/j.1460-2075.1986.tb04630.x
|View full text |Cite
|
Sign up to set email alerts
|

A 22-kd protein (sorcin/V19) encoded by an amplified gene in multidrug-resistant cells, is homologous to the calcium-binding light chain of calpain.

Abstract: We have previously shown that at least five linked genes are co‐amplified and overexpressed in the multi‐drug resistant (MDR) Chinese hamster ovary cell line CHRC5. We show here that one of these genes (class 4) codes for a small phosphorylated, cytosolic protein, sorcin/V19, known to be overproduced by many MDR cell lines. The class 4 gene codes for a nested set of mRNAs, varying in size between 1000 and 2500 nucleotides. Sequence analysis of complementary DNAs shows that these mRNAs encode a protein of 198 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
94
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 66 publications
(40 reference statements)
2
94
0
Order By: Relevance
“…These findings are consistent with the presence of two EF-hand calcium binding motifs and two putative protein kinase A recognition sites in the C-terminal domain of the sorcin sequence [4]. The N-terminal domain of the sequence is rich in glycine, proline and tyrosine residues and is homologous to the corresponding domain of the calpain light chain where it is involved in heterodimer formation [4].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…These findings are consistent with the presence of two EF-hand calcium binding motifs and two putative protein kinase A recognition sites in the C-terminal domain of the sorcin sequence [4]. The N-terminal domain of the sequence is rich in glycine, proline and tyrosine residues and is homologous to the corresponding domain of the calpain light chain where it is involved in heterodimer formation [4].…”
Section: Introductionsupporting
confidence: 67%
“…Direct calcium binding studies and in vitro phosphorylation assays have shown that sorcin purified from heart and sorcin-overproducing cultured cells binds Ca 2+ and is phosphorylated by the protein kinase A catalytic subunit [1,5,7,8]. These findings are consistent with the presence of two EF-hand calcium binding motifs and two putative protein kinase A recognition sites in the C-terminal domain of the sorcin sequence [4]. The N-terminal domain of the sequence is rich in glycine, proline and tyrosine residues and is homologous to the corresponding domain of the calpain light chain where it is involved in heterodimer formation [4].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…From sequence comparisons it appeared that the ALG-2 protein contains five EF-hands, with two of them being functional in 45 Ca 2ϩ overlay experiments (13), and furthermore it shares homology with members of the PEF (penta EF-hand) family, which includes sorcin (16), grancalcin (17), calpain light chain (18), yeast hypothetical protein of 38.4 kDa (19), and peflin (20). These proteins contain a glycine-rich N-terminal region proposed to play an important role in Ca 2ϩ -dependent membrane binding (19).…”
mentioning
confidence: 99%
“…Studies using in vitro derived multidrugresistant (MDR) cell lines have shown that MDR is often associated with over-production of two groups of proteins: the P-glycoproteins (for review see which have drug-binding properties (Safa et al, 1986) and are thought to function as a membrane anchored efflux pump for multiple drugs (Willingham et al, 1986); and sorcin/CP22 (Meyers et al, 1985;Meyers & Biedler, 1981;Koch et al, 1986;Martinnson et al, 1985;Shen et al, 1986a; Van der Bliek et al, 1986a), a small cytosolic calcium-binding protein. Considerable evidence supports the hypothesis that it is P-glycoprotein that is responsible for MDR in almost all cell lines examined (Debenham et al, 1982;Gros et al, 1986;Kartner et al, 1983;Robertson et al, 1984;Scotto et al, 1986;Shen et al, 1986b;Van der Bliek et al, 1986b).…”
mentioning
confidence: 99%